The role of lizardfish trimethylamine-N-oxide demethylase in the aggregation of muscle during frozen and children storage - Kittima Leelapongwattana (Prince of Songkla University, 2007)
Thesis (Ph.D., Food Technology)--Prince of Songkla University, 2007